Meningitis mortality in Neurology Ward of Dr. Cipto Mangunkusumo hospital Jakarta (Faculty of Medicine Universitas Indonesia, 2006)
Mortality rate of meningitis is not decreased even though there is decreasing meningitis rate and advanced development of antibiotics. The purpose of this study is to find out meningitis mortality pattern and to evaluate factors related to meningitis mortality in hospitalized patients. Study was done using retrospective data from medical records of the patients administered in the Neurology ward of Cipto Mangunkusumo hospital from January 1997 — December 2005. Data were reported descriptively in texts and tables, and analyzed with Chi-square for categorical data and Student's